PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK BERBANTU MODEL COOPERATIVE TYPE SCRAMBLE TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI KELAS X SEMESTER GANJIL SMA NEGERI 1 BANDAR SRIBHAWONO TAHUN PELAJARAN 2019/2020 - Nawang Putri Lestari; Ningrum Ningrum; Meyta Pritandhari (Universitas Muhammadiyah Metro, 2021)
Student Worksheet (LKPD) is a teaching material used by teachers to support the learning process. Containing material sheets and assignments that must be done, LKPD is also used to optimize student activities in learning. The scramble type of cooperative model is learning to practice the accuracy and speed of answering questions. Students must combine the right brain and the left brain. Not only that, students also have to guess quickly the answers to the questions that are available but are still in random conditions. Based on the results of a survey conducted by researcher at SMA Negeri 1 Bandar Sribhawono as well as information from teachers in the field of economic studies, it was found that there are still many students in Grade X social studies whose learning outcomes are not yet complete. Based on these problems, the formulation of the problem in this study is whether there is an influence on the use of LKPD Assisted by the Scramble Type of Cooperative Model on the Learning Outcomes of Economic Subjects in Class X Odd Semester of SMA S 1 Bandar Sribhawono Academic Year 2019/2020?